2017
DOI: 10.1021/acs.biochem.7b00560
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Dimer Exchange Interface of the Bacterial DNA Damage Response Protein UmuD

Abstract: The Escherichia coli SOS response, an induced DNA damage response pathway, confers survival on bacterial cells by providing accurate repair mechanisms as well as the potentially mutagenic pathway translesion synthesis (TLS). The umuD gene products are upregulated after DNA damage and play roles in both nonmutagenic and mutagenic aspects of the SOS response. Full-length UmuD is expressed as a homodimer of 139-amino-acid subunits, which eventually cleaves its N-terminal 24 amino acids to form UmuD'. The cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…UmuD and UmuD′ exist as homodimers, but their subunits can readily exchange to form UmuDD′ heterodimers preferentially. Murison et al () measured the kinetics of exchange of a number of fluorescently labeled single‐cysteine UmuD variants and demonstrated that somewhat different molecular surfaces mediate homodimer exchange and heterodimer formation. Importantly, in the heterodimer context, UmuD′ is specifically degraded by the ClpXP protease (Frank et al, ).…”
Section: Tls Polymerasesmentioning
confidence: 99%
“…UmuD and UmuD′ exist as homodimers, but their subunits can readily exchange to form UmuDD′ heterodimers preferentially. Murison et al () measured the kinetics of exchange of a number of fluorescently labeled single‐cysteine UmuD variants and demonstrated that somewhat different molecular surfaces mediate homodimer exchange and heterodimer formation. Importantly, in the heterodimer context, UmuD′ is specifically degraded by the ClpXP protease (Frank et al, ).…”
Section: Tls Polymerasesmentioning
confidence: 99%
“…After this, the expression of SOS-related genes is activated, resulting in the inhibition of the cell division process, in order to repair the DNA [13,18]. However, when the integrity of both DNA strands is affected, the expression of error-prone DNA polymerases is activated and their low fidelity might result in bacterial mutagenesis [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In response to DNA damage (e.g., caused by UV radiation), umuCD -encoded DNA polymerase of the Y family, enables DNA synthesis past lesions in the template strand. Therefore, the umuCD genes play an important role in maintaining genome stability in bacteria (Goodman et al, 2016; Murison et al, 2017). Genomic analysis revealed that these DNA repair systems are often found within plasmids of cold-active bacteria, especially those originating from polar regions (Dziewit and Bartosik, 2014).…”
Section: Resultsmentioning
confidence: 99%